Analysis of human errors in emergency steering gear operation at tanker ship under decomposed fuzzy analytical hierarchy process and SLIM approach - Akyuz, Emre; Cebi, Selcuk (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Emergency steering gear operation at tanker ships is a safety-critical task requiring utmost effort in case of steering system failure. Therefore, ship crew performance plays significant role. The objective of this article is to systematically identify and quantify human errors associated with emergency steering gear operations. To fulfil this, a robust and practical approach Decomposed Fuzzy Analytical Hierarchy Process (DF-Fuzzy AHP) and Success Likelihood Index Methodology (SLIM) is integrated. The proposed approach allows for the structured assessment of performance shaping factors (PSFs) while effectively addressing the vagueness and subjectivity in expert opinions. The findings of the article show that task 4-inappropriate manoeuvres made/engine(s) stoppedis having the highest human error probability (2.185E-01) value. Besides its robust theoretical background, the outcomes of the research will provide utmost practical contributions ship safety professionals, tanker ship owners, superintendents and HSEQ managers to enhance operational safety and prevent potential failures of ship crew during operational process of emergency steering gear at tankers.
Keywords: Human error; Decomposed fuzzy AHP; Emergency steering gear; System safety; PROBABILITIES; Engineering; Oceanography